2017
DOI: 10.1093/ckj/sfw146
|View full text |Cite
|
Sign up to set email alerts
|

Soluble klotho may be a marker of phosphate reabsorption

Abstract: Background: Membrane-bound α-klotho functions as a co-receptor with fibroblast growth factor receptor at the renal tubule conferring specificity to fibroblast growth factor-23 (FGF-23), allowing it to inhibit tubular phosphate reabsorption at physiological concentrations. α-klotho also exists as a soluble protein. However, the complex interrelationships between soluble α-klotho (sKl), FGF-23 and phosphate reabsorption are poorly understood, with little known about the links between sKl, FGF-23 and phosphate re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 51 publications
1
7
1
1
Order By: Relevance
“…This could be attributed to the fact that phosphaturia characterizes more advanced CKD stages which are also characterized by lower sKlotho plasma levels. The significant difference of sKlotho plasma levels among CKD stages, as well the independent correlation of sKlotho with mGFR and phosphate in multiple regression analysis, confirmed the already recognized relationship of sKlotho with renal function and phosphate [48]. In contrast with other studies, patients with DM had lower sKlotho plasma levels [49].…”
Section: Cfgf-23 and Sklotho Associations With Cardiovascular Risk Fasupporting
confidence: 82%
“…This could be attributed to the fact that phosphaturia characterizes more advanced CKD stages which are also characterized by lower sKlotho plasma levels. The significant difference of sKlotho plasma levels among CKD stages, as well the independent correlation of sKlotho with mGFR and phosphate in multiple regression analysis, confirmed the already recognized relationship of sKlotho with renal function and phosphate [48]. In contrast with other studies, patients with DM had lower sKlotho plasma levels [49].…”
Section: Cfgf-23 and Sklotho Associations With Cardiovascular Risk Fasupporting
confidence: 82%
“…Clinical studies in patients with CKD have shown that soluble klotho is lower than normal (519 ± 183 versus 845 ± 330 pg/mL, P < .0001) in renal patients, and soluble klotho is positively correlated with serum calcium and negatively correlated with serum phosphate, PTH, and FGF23, suggesting that soluble klotho might reflect the ensuing tubular resistance to FGF23, which could be an early marker of CKD-MBD [ 143 , 144 ]. Recently, another clinical study suggested that soluble klotho is significantly associated with phosphate reabsorption independently of FGF-23, which may be a marker of phosphate reabsorption [ 145 ]. Therefore, soluble klotho seems to be a marker for disorders of phosphate and bone metabolism in CKD.…”
Section: Main Textmentioning
confidence: 99%
“…The advances in Klotho biology described above may have major implications for the pathophysiology of renal disease. There is good evidence from clinical and experimental studies that both acute and chronic renal failure are associated with reduced expression of Klotho in the kidney, and with reduced sKlotho levels in the blood [ 43 ▪▪ , 44 47 ]. In agreement with these data, kidney transplantation in CKD patients results in a rapid rise in circulating sKlotho, and a decline in circulating FGF23 levels [ 48 ▪ , 49 ▪ ].…”
Section: Pathophysiological Role Of Klotho In Acute and Chronic Renalmentioning
confidence: 99%